Operationalizing Kuntowijoyo's Islamization of Knowledge: Methods and Relevance for Contemporary Indonesia - Abdul Manaf Lubis; Siti Hajar; Axesa Haraja Saputra (MADINAH, 2026)
This study aims to operationalize Kuntowijoyo’s concept of the Islamization as science by examining its methodological framework and its relevance in the contemporary Indonesian context. Existing studies on Kuntowijoyo’s thought have largely focused on its philosophical and epistemological dimensions, with limited attention given to its practical application as an operational methodological system. This article addresses this gap by analyzing five key methods proposed by Kuntowijoyo: transcendental structuralism, the analytic–synthetic method, the objectification method, the historical–empirical method, and the prophetic method (normative–transformative). Using a qualitative approach based on literature review, this study demonstrates that these methods can be operationalized in various socio-religious contexts in Indonesia, including the development of Islamic financial institutions, socio-religious movements, and community-based practices. The findings indicate that the Islamization of knowledge is not merely a normative or abstract project, but a methodological framework capable of transforming Islamic values into empirical and institutional forms. This study contributes to the development of Prophetic Social Science by offering a more applied and context-sensitive interpretation of Kuntowijoyo’s thought, particularly in addressing the challenges of contemporary Indonesian society.